1st Snow Data Assimilation Workshop in the framework of COST HarmoSnow ESSEM 1404 - Jürgen Helmert; Martin Lange; Jiarui Dong; Patricia de Rosnay; David Gustafsson; Evgeniy Churulin; Ekaterina Kurzeneva; Richard Müller; Jörg Trentmann; Niels Souverijns; Roland Koch; Uwe Böhm; et al. (Meteorologische Zeitschrift, 2018)
The 1st Snow Data Assimilation Workshop, organized under the COST Action ESSEM 1404 HarmoSnow, took place in Offenbach, Germany, on 8–9 March 2017. Of particular relevance for the workshop were thematic sessions on i) data assimilation methods and the use of snow observations, ii) snow observations and evaluation, iii) snow observations and physical snow models, and iv) snow observations and hydrological models. This report summarizes the scientific contributions presented at the workshop. The discussions mainly focused on methods for combining satellite observations with conventional in-situ snow measurements and modeling results, as well as on errors in the spatial and temporal representation of snow measurements for data assimilation in NWP and hydrological models. It has been shown that the assimilation of in-situ and satellite-based snow observations improves the quality of the snow analysis and forecast. However, in order to achieve this positive impact, a thorough quality control of the observational data is necessary, in particular because of the automation of the ground-based networks.